Integrated Morphological, Phenotypic, and Biochemical Profiling of Juglans regia Genotypes within Agroforestry Systems of North Western Himalaya - Baksh, Megna Rashid; Bakshi, Megna (Indian Journal of Agroforestry, 2026)
The present investigation, entitled “Morpho-phenotypic and biochemical characterisation of Juglans regia genotypes in the agroforestry systems at Benhama, Ganderbal” was conducted on an eight-year-old walnut plantation with 7m×7m spacing grown along with forage crops. A total of 5 genotypes, CITH-Walnut-1, CITH-Walnut-2, CITH-Walnut-3, Sulaiman and Hamdan were selected as treatments with 4 replications each for the study. The investigations revealed that the cultivar and environment have an impact on flowering characteristics. For all five types of walnuts, the peak blooming dates were found to be in early to mid-April. The maximum values for tree height (3.51 m), tree diameter (12.81 cm), leaf length (17.68 cm), number of male catkins per cluster (4.00), nut diameter (44.66 mm), nut length (46.44 mm), nut weight (24.73 g), kernel weight (13.61 g) and yield (0.71 t ha-1) was recorded for CITH-Walnut-1 genotype. The maximum values for total phenols (47.89 mg/g GAE), flavanols and flavonoids (10.07 mg/g QE), antioxidants (752.42 µM Fe2+/g FW) and oil content (52.14 %) were recorded for CITH-Walnut-3 genotype. GC-MS results showed the presence of many compounds in all five varieties, particularly linoleic acid and palmitic acid. CITH-Walnut-1 outperformed other varieties in terms of growth and yield parameters, while CITH-Walnut-3 outperformed other varieties in terms of biochemical activity. Principal component analysis revealed that three of the four components had eigenvalues larger than unity. The first two components were retained for further analysis, as they account for 81.12% of the total variation. A cluster analysis of five genotypes was conducted to assess the relationships between the selected genotypes in a dendrogram. The cluster dendrogram divided the genotypes into four categories